The Mesoscopic Modeling of Burst Suppression during Anesthesia - Liley, David; Walsh, Matthew (Frontiers in Computational Neuroscience, 2013)
The burst suppression pattern is well recognised as a distinct feature of the mammalian electroencephalogram (EEG) waveform. Consisting of alternating periods of high amplitude oscillatory and isoelectric activity It can be induced in health by deep anaesthesia as well as being evoked by a range of pathophysiological processes that include coma and anoxia. While the electroencephalographic phenomenon and clinical implications of burst suppression have been studied extensively, the physiological mechanisms underlying its emergence remain unresolved and obscure. Because electroencephalographic bursting phenomenologically resembles the bursting observed in single neurons, it would be reasonable to assume that the theoretical insights developed to understand bursting at the cellular (``microscopic'') level would enable insights into the dynamical genesis of bursting at the level of the whole brain (``macroscopic''). In general action potential bursting is the result of the interplay of two time scales: a fast time scale responsible for spiking, and a slow time scale that modulates such activity. We therefore hypothesise that such fast-slow systems dynamically underpin electroencephalographic bursting. Here we show that a well known mean field dynamical model of the electroencephalogram, the Liley model, while unable to produce burst suppression unmodified, is able to give rise to a wide variety of burst-like activity by the addition of one or more slow systems modulating model parameters speculated to be major ``targets'' for anaesthetic action. The development of a physiologically plausible theoretical framework to account for burst suppression will lead to a more complete physiological understanding of the EEG and the mechanisms that serve to modify ongoing brain activity necessary for purposeful behaviour and consciousness.